Āṭhavāñce jhele - Geḍāma, Lakṣmīkamala (Padmagandhā Prakāśana, 2016)
Autobiographical reminiscences of Lakshmīkamala Geḍāma, Marathi author
In Marathi
Keywords: Autobiografie; Geḍāma; Lakshmīkamala; Authors; Marathi